Warneckea albiflora, a new species of W. subgenus Carnosae (Melastomataceae—Olisbeoideae) from coastal dry forest in northern Mozambique - Stone, Robert Douglas; Tenza, Ntombiphumile Perceverence (Phytotaxa, 2017)
Described and illustrated is Warneckea albiflora R.D. Stone & N.P. Tenza, another localized endemic of coastal dry forest near Quiterajo in Mozambique’s Cabo Delgado Province. In Flora Zambesiaca the new species would key to Memecylon sansibaricum Taub. [≡Warneckea sansibarica (Taub.) Jacq.-Fél.], but is distinguished by its elliptic-lanceolate, attenuate–acuminate leaves and white flowers borne on pedicels 3.5–4 mm long (versus leaves elliptic and rounded to shortly and obtusely acuminate, pedicels 6–15 mm long, and flowers pale blue to deep blue in Warneckea  sansibarica). Because of its evidently very limited occurrence as well as on-going anthropogenic threats, Warneckea albiflora is provisionally assessed as Critically Endangered (CR) B1ab(iii) according to IUCN criteria. A key is provided to the Mozambican species of Warneckea.